Comparative study of 316L depositions by two welding current processes. Issue 13 (3rd October 2019) - Wu, Wei; Xue, Jiaxiang; Zhang, Zhanhui; Yao, Ping
ABSTRACT: Wire and arc additive manufacturing (WAAM) has advantages of high efficiency and low cost. However, different welding current processes lead to different heat input and repeated heating treatment during the deposition process, which has an influence on the forming and performance. In this study, 30 layers of reciprocating depositions for 316L stainless steel were carried out by speed cold and speed arc welding processes, and the morphology, effective deposition rate per power, microstructure, and properties of depositions were compared. The outcomes indicated that different welding current processes make different shaping appearances, and the effective deposition rate per power of speed cold welding is 15.2% higher than that of speed arc welding. The microstructures of depositions are columnar crystals; however, the higher power of speed arc welding leads to the coarse structure, and the enhanced thermal cycle and preheating effect produce a uniform hardness and 4.9% higher tensile strength, but lower toughness than those of speed cold welding. Due to the direction of deposition, the tensile strength of depositions by two processes has obvious anisotropy that can reach to 8.18% and 13.3%, respectively.